Sociolinguistics and social contexts of language : an assessment through on-line chatting - Chehimi, Ghada Mohammad (Beirut Lebanese American University- School of Arts and Sciences - Department of Education., 2002)
Being an English teacher I have noticed a sense of instability in the use of languages. Students are not sure what Language to use and when. This needs special attention and guidance from language teachers whether the language used is the native Arabic or any other foreign language. Moreover, the use of the Internet and chatting, in particular, has negatively affected the use of language in the classroom as an academic language. Students have started writing their English essays using the same style they use in chatting, that is, by using symbolic and abbreviated terms embedded in their usual text; this is the result of neglect of language teachers who are not giving appropriate directions to their students. To prevent using chatting is impossible. However, to reinforce language learning, teachers may use the chat tool. They can create chat rooms for their classes where only the target language in its appropriate form can be used. Definite instructions must be available for students at all times. Besides, under such an environment, the whole conversation may be recorded and used as reference for further lessons by both the teachers and the students. However, such facility is not possible under present academic conditions. This research project shall shed light and asses how Lebanese choose their language while carrying an on-line conversation and to explore the variations governed by sociolinguistics characterizing the Lebanese chatting community. The intention is, to quantitatively and qualitatively describe the computer literacy of the selected sample and how this is interrelated to the choice of chatting language within the frame of rules that the virtual community is abiding by.
: Mémoire
Keywords: English Language Education School Evaluation; L enseignement de la Langue Anglaise Evaluation Scolaire; Milieu Socio-Culturel; Socio-Cultural Milieu